Treatment of LF Slag to Prevent Powdering during Cooling - Ghorai, Satadal; Mandal, Gopi K; Roy, Syamantak; Minj, R K; Agrawal, Archana; Singh, D P; Kumar, Alok; Ramana, R. B. V (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
The polymorphic transformation of the monoclinic β-polymorph to the orthorhombic γ-polymorph of di-calcium silicate at around 500°C during cooling results in disintegration of slag. The slag generated during the production of TMT grade steel in ladle furnace at Tata steel Jamshedpur behaves similar manner. An attempt has been made to prevent this crumbling.  The experiments were conducted in 10 kg air induction furnace. Various types of silica source were used to reduce the basicity of the LF slag does not crumble. Optimization of the additives percentage and the optimum basicity was determined. Also, various types of additives like borax and barium carbonate were used to stabilize the β phase. Also the results indicate that 0.2% boarx, 2% barium carbonate and 1.7 basicity is required to prevent dusting. TCILP test (USEPA test no 1131) of the borax and barium carbonate treated samples indicate that barium carbonate treated slag contain high barium level. Therefore, it can not be used for the dusting prevention.